The IASP classification of chronic pain for ICD-11 - chronic primary pain - Nicholas, Michael; Treede, Rolf-Detlef (Pain, 2019)
AbstractThis article describes a proposal for the new diagnosis of chronic primary pain (CPP) in ICD-11. Chronic primary pain is chosen when pain has persisted for more than 3 months and is associated with significant emotional distress and/or functional disability, and the pain is not better accoun